A mesocosm concept for the simulation of near‐natural shallow underwater climates: The Kiel Outdoor Benthocosms (KOB). (1st August 2015) - Wahl, Martin; Buchholz, Björn; Winde, Vera; Golomb, Dar; Guy‐Haim, Tamar; Müller, Jens; Rilov, Gil; Scotti, Marco; Böttcher, Michael E.
Abstract: Biogenic, seasonal, and stochastic fluctuations at various scales characterize coastal marine habitats and modulate environmental stress. The relevance of most past studies into climate change impacts is weakened by the usually intentional exclusion of fluctuations from the experimental design. We describe a new outdoor mesocosm system for benthic research ("benthocosms") which permit the control and manipulation of several environmental variables while admitting all natural in situ fluctuations. This is achieved by continuously measuring the relevant variables (e.g., temperature, pH, O2, CO2 ) in situ, defining these in real time as reference values in the control software and simulating target climates by delta treatments. The latter constitute the manipulative addition of predefined changes (e.g., "warming", "acidification") to the reference values. We illustrate the performance of the system by presenting the environmental data of four seasonal experiments which together represent an entire year. The "Kiel Outdoor Benthocosms" allow realizing near‐natural climate change experiments on complex benthic communities under controlled scenarios.